A disseminação da informação sobre brinquedos e brincadeiras antigas no Centro Educacional Doce Mel - MOURA, Daniela Albuquerque (2017)
This is to know the old toys and games seeking its dissemination, importance in the play and in the development of the child. The objective was to perform the work at the Centro Educacional Doce Mel, where it was presented children toys and prank ancient, showing each one of them so that later they could experience them, as well as their origin and forms of play. A bibliographical research and descriptive also with qualitative and quantitative approaches. For data collection was applied a questionnaire directed to the school teacher, form for children and the realization of participant observation made by the author of the survey. We analyzed the importance of dissemination of information about the toys and game in school and the contribution of these pranks ancient for the socialization of children. It was observed that the dissemination is very important because it contributes to the continuity of these toys and games that are part of the history of mankind, being fundamental to the socialization of children.